Effect of some organic fillers on the mechanical properties of high density polyethylene - F. AL-Zamili, Taleb; A . Abass, Mohammed; A . Najim, Ahmed (University of Thi-Qar Journal of Science, 2019)
In this paper , the mechanical properties of high density polyethylene (HDPE grade M624) produced by SCPI / Basrah – Iraq , mixed with the wood flour and bagasse as fillers with 10-50 % w/w have been studied . The maximum tensile strength was observed at 10% w/w of fillers ratio . The elongation , impact strength and fracture energy were decreased with increasing of fillers ratio while the Young modulus and hardness were increased .